The Critical Role of State-owned Enterprises and Development Finance Institutions in Black Economic Empowerment :The case of Eskom, IDC and the DBSA - Mondi, Lumkile (Southern Centre for Inequality Studies (SCIS), 2021)
The underlying motivation for the establishment of state-owned entities and development of finance institutions was to provide the state with instruments to enable the building of a diversified industrial economy. Under the colonial and apartheid government, these were to play a key role in racially based job segregation and Afrikaner empowerment. This paper explores the role of Eskom, the IDC and DBSA during the democratic period in deracialising the economy through black economic empowerment. It explains the political and economic forces underlying the often failed efforts to reform Eskom in the face of power shortages, financial difficulties, questionable investment in capacity and economic empowerment. The paper shows how the IDC and the DBSA have contributed to black economic empowerment. Finally, the paper provides a window into understanding the policy trajectory and decision-making of the South African government as it deals with the competing challenges of business interests and black entrepreneurs long denied economic participation because of the injustice of apartheid.
Keywords: Black Economic Empowerment; Establishment of state-owned entities; Development of finance institutions; Diversified industrial economy; Eskom; IDC; DBSA